Rational emotive behaviour therapy in a nutshell - Neenan, Michael (Counselling in a nutshell series, 2011)
The book presents the key elements of rational emotive behaviour therapy (REBT), both theory and practice, accessibly and in as few words as possible - it is a primer on REBT for beginning counsellors or those who want a straightforward overview.